2016
DOI: 10.1002/2016gl070189
|View full text |Cite
|
Sign up to set email alerts
|

The permeability of the magnetopause to a multispecies substorm injection of energetic particles

Abstract: Leakage of ions from the magnetosphere into the magnetosheath remains an important topic in understanding the plasma physics of Earth's magnetopause and the interaction of the solar wind with the magnetosphere. Here using sophisticated instrumentation from two spacecraft (Radiation Belt Storm Probes Ion Composition Experiment on the Van Allen Probes and Energetic Ion Spectrometer on the Magnetospheric Multiscale) spaced uniquely near and outside the dayside magnetopause, we are able to determine the escape mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
19
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 26 publications
(48 reference statements)
9
19
0
Order By: Relevance
“…Kelvin-Helmholz wave generation is one mechanism highlighted by Sorathia et al (2017). Here we would only proclaim that the observations of Westlake et al (2016) and Cohen et al (2016) of oxygen ions in the magnetosheath provide no support for escaping configurations. We have shown that those oxygen ions did not in fact escape but were entrained at the boundary executing Speiser-like orbits (see Event 1 discussed in section 2.1.1).…”
Section: 1029/2019ja026626mentioning
confidence: 67%
“…Kelvin-Helmholz wave generation is one mechanism highlighted by Sorathia et al (2017). Here we would only proclaim that the observations of Westlake et al (2016) and Cohen et al (2016) of oxygen ions in the magnetosheath provide no support for escaping configurations. We have shown that those oxygen ions did not in fact escape but were entrained at the boundary executing Speiser-like orbits (see Event 1 discussed in section 2.1.1).…”
Section: 1029/2019ja026626mentioning
confidence: 67%
“…Energetic particle (greater than or equivalent to tens of keV) escape from the magnetosphere has received renewed interested recently due to in situ observations made by the Magnetospheric Multiscale (MMS) mission at the dayside magnetopause [ Cohen et al , ; Westlake et al , ]. Historically, observations of magnetospheric ions and electrons in the magnetosheath have been associated with either finite Larmor radius effects [e.g., Sibeck et al , ; Kudela et al , ] or magnetic reconnection [e.g., Korth et al , ; Mitchell et al , ], the former mechanism favored due to poor correlation of particle escape with conditions required for reconnection [ Sibeck et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Westlake et al [] used observations during the same MMS magnetopause crossing to highlight marked differences in the particle signatures of escape of the light (H and He) and heavy (O) ions. The observations showed specific agyrotropic signatures in the O distributions suggesting that the heavy ions were entrained within the boundary and drifted duskward, while the lighter ions escaped along the reconnected field lines.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to highlight the novelty of the statistical study presented here amidst the extremely rich history of the study of energetic electrons beyond the magnetopause, a substantial (but admittedly nonexhaustive) literature review is provided in section 1.1. It must be emphasized that this paper (and the review included) will focus specifically on observations of energetic (greater than tens of keV) electrons observed in the magnetosheath and upstream of the bow shock and is independent of the extremely rich literature regarding the well‐documented history of lower energy (eV to several keV) particles at/beyond the magnetopause [e.g., Freeman et al , ; Montgomery et al , ; Scarf et al , ; Hones et al , ; Scudder et al , ; Reasoner , ; Eastman et al , ; Cowley , ; Fuselier et al , , ; Lefebvre et al , ; Lee et al , , and references therein] and observations of escaping magnetospheric ions [e.g., West and Buck , ; Anagnostopoulos et al , ; Sibeck et al , , ; Zong et al , ; Eccles and Fritz , ; Kronberg et al , ; Westlake et al , , and references therein], upstream ion events [e.g., Asbridge et al , ; Lin et al , ; Scholer et al , , ; Desai et al , , and references therein], and shock‐related ion acceleration [e.g., Ipavich et al , ; Gosling , ; Armstrong et al , ; Forman and Webb , ; Scholer , ; Thomsen , ; Sibeck et al , ; Burgess et al , ; Lee et al , , and references therein]. We focus here on electrons because ions have a broader array of escape mechanisms [ Mauk et al , ] that make their study substantially more complex.…”
Section: Introductionmentioning
confidence: 99%